(3CRgGQ GdQhVGJ TQM QhVGJ GdLfGfs - (3GdGbMUGQj, MSf Hf WhQNGf Hf OGhO Hf jYbhH, (B1025 (3g`s ((3GdSjO MGaX eUWai GdQTOj Hf EHQGgje GdbjQTgQj (B( (3GdeOQS HOGQ GdSdcfI GdSfjI GdbSWfWjfjI (B)s)
(3ChdgG (B:s
(3GdMeO ddg bOje GdPGJ hGdUaGJ Ef Chd eG jH Ydi GdHTQ gh eYQaI Gddg JYGdi HGdGSJOdGd hGdfXQ Ke GdGgJOGA Edi GdNjQ hGdGfJgGA Yf GdTQ hPdc dG jJCJi EdG HGdEjeGfs
(3BNQgG (B:s
(3afSH gPg GdRjGQI Edi Jdc GdWGYI HfGA Ydi Yde Gddg JYGdi hGdCde aj GdeVQhH YbjH GdVQH hGdGfcSGQ YbjH GdcSQI hGdehJ YbjH GdbJd cd Pdc eNdhb hGdMeO ddg QH GdYGdejfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B2 / 194s
(3EjVGM Gdecfhf (B1 / 586s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds